1988
DOI: 10.1007/bf00035751
|View full text |Cite
|
Sign up to set email alerts
|

In vitro organogenesis and somatic embryogenesis from punctured leaf of Populus nigra � P. maximowiczii

Abstract: Various explant sources of Populus nigra x P. maximowiczii were used to examine the effects of growth hormones on morphogenesis in vitro. Initial experiments indicated that punctured leaves were superior to non-punctured ones for both callus growth and formation of shoots and roots on MS medium containing various types and concentrations of growth hormones. After 6 weeks in culture, an average of 178 shoots, 129 roots and 3.1 g fresh weight of callus were directly produced from the abaxial side of each punctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This may be due to an improved access of plant growth regulators or translocatable wound response factors. The stimulating effect of puncturing on in vitro shoot formation has been observed in Populus as well (Park & Son 1988). Adding a transformation procedure to this regeneration protocol markedly reduced the number of adventitious shoots.…”
Section: Discussionmentioning
confidence: 88%
“…This may be due to an improved access of plant growth regulators or translocatable wound response factors. The stimulating effect of puncturing on in vitro shoot formation has been observed in Populus as well (Park & Son 1988). Adding a transformation procedure to this regeneration protocol markedly reduced the number of adventitious shoots.…”
Section: Discussionmentioning
confidence: 88%
“…BA also showed toxic effects when it was used to induce shoot formation from callus. Although BA is widely used in tissue culture of Populus (Park & Son 1988;Russell & McCown 1988;Sellmer & McCown 1989;De Block 1990), toxicity has been reported (Coleman & Ernst 1989).…”
Section: Discussionmentioning
confidence: 99%
“…cell group, leading to further proliferation of single cells or smaller groups. A related study was reported on the promotion of organogenesis and somatic embryogenesis in punctu/ed leaf of Populus nigra x P. maxiraowiczii, a woody species (Park & Son 1988). It can be inferred that the induction of direct somatic embryogenesis observed from hyperhydrated plantlets is an alternative pathway for the expression of stress response of the hyperhydrated tissue.…”
Section: Discussionmentioning
confidence: 99%